2008
DOI: 10.1128/jb.01864-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tryptophan Residues in the Staphylococcal Multidrug Transporter QacA Reveals Long-Distance Functional Associations of Residues on Opposite Sides of the Membrane

Abstract: Tryptophan residues can possess a multitude of functions within a multidrug transport protein, e.g., mediating interactions with substrates or distal parts of the protein, or fulfilling a structural requirement, such as guiding the depth of membrane insertion. In this study, the nine tryptophan residues of the staphylococcal QacA multidrug efflux protein were individually mutated to alanine and phenylalanine, and the functional consequences of these changes were determined. Phenylalanine substitutions for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…[75] Site-directed mutagenesis studies with QacA produced interesting results, for example, a tryptophan-to-alanine change in the outside surface was compensated by changes in the inside loops of the protein. [76] An in-vitro study revealed that EmrAB of E. coli forms a dimer in contrast to the trimeric RND AcrB. [77]…”
Section: Drug Efflux Pumps In Bacteria: Structures and Mechanismsmentioning
confidence: 99%
“…[75] Site-directed mutagenesis studies with QacA produced interesting results, for example, a tryptophan-to-alanine change in the outside surface was compensated by changes in the inside loops of the protein. [76] An in-vitro study revealed that EmrAB of E. coli forms a dimer in contrast to the trimeric RND AcrB. [77]…”
Section: Drug Efflux Pumps In Bacteria: Structures and Mechanismsmentioning
confidence: 99%
“…Genes were amplified by PCR with Pfx supermix (Invitrogen) and cloned into the pTTQ18-RGSH6 vector as reported (7). Site-directed mutagenesis was conducted by using the QuikChange method as described (30), but using KOD hot start polymerase (Novagen). The ACIAD1978 gene was deleted from the A. baylyi ADP1 genome by allelic exchange as described (31).…”
Section: Methodsmentioning
confidence: 99%
“…This is not surprising per se because Trp residues in transmembrane proteins have special properties that can facilitate long-distance functional associations on opposite sides of the membrane. For example, in the staphylococcal multidrug transporter QacA, a number of Trp residues appear to be located at the periphery of transmembrane segments, where they guide the depth of the transmembrane insertion (47). Aromatic stacking interactions accommodated by Trp residues may also assist the stable binding of aromatic substrates.…”
Section: Self-limitation Of Trp Import Caused By Trp Starvationmentioning
confidence: 99%